Cavitation on hydrofoils with leading edge protuberances. (15th August 2018) - Custodio, Derrick; Henoch, Charles; Johari, Hamid
Abstract: Cavitation characteristics and hydrodynamic forces of hydrofoils with bioinspired, wavy leading edges were examined experimentally in a water tunnel. Force measurements were carried out using a waterproof load cell, and cavitation patterns were recorded by directly imaging the hydrofoil surface. All semi-span hydrofoils had an underlying NACA 634 -021 profile with either a rectangular or swept leading edge planform. The sinusoidal leading edge geometries were defined by three amplitudes of 2.5%, 5%, and 12% and two wavelengths of 25% and 50% of the mean chord length. Results revealed that cavitation on the modified hydrofoils with the two larger amplitudes was largely confined to the regions directly behind the protuberance troughs, whereas a baseline with flat leading edge and the smaller amplitude hydrofoils exhibited sheet cavitation over the entire span. Additionally, cavitation on the modified hydrofoils appeared at consistently lower angles of attack than on the baseline model. Lift coefficient for the baseline model was generally comparable to or greater than that of the modified hydrofoils at the angles of attack considered. Except for the largest amplitude hydrofoils, drag for the modified hydrofoils was equal to the baseline model for nearly the entire angle of attack range. Highlights: Cavitation characteristics and forces on hydrofoils with sinusoidal leading edge were studied in a water tunnel at angles up to 30°. Cavitation on the modified hydrofoils with larger amplitude protuberances was largely confined to the regions directly behind the troughs. Cavitation on the modified hydrofoils appeared at consistently lower angles than on the baseline hydrofoil. Lift of the leading edge modified hydrofoils was less than or equal to that of the baseline hydrofoil at nearly all angles. Drag of the modified hydrofoils was comparable to the baseline hydrofoil for the majority of angles.